2008
DOI: 10.1103/physreva.78.022317
|View full text |Cite
|
Sign up to set email alerts
|

Thermal equilibrium as an initial state for quantum computation by NMR

Abstract: We present a method of using a nuclear magnetic resonance computer to solve the Deutsch-Jozsa problem in which: (1) the number of molecules in the NMR sample is irrelevant to the number of qubits available to an NMR quantum computer, and (2) the initial state is chosen to be the state of thermal equilibrium, thereby avoiding the preparation of pseudopure states and the resulting exponential loss of signal as the number of qubits increases. The algorithm is described along with its experimental implementation u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 36 publications
0
22
0
3
Order By: Relevance
“…Second, it is known that using ancilla qubits entangled with "system" qubits enhances the possibility of successful discrimination between unitaries [11] and it is conceivable that this could also yield a larger set of quantum algorithms and improved lower bounds in the thermal equilibrium case. Finally, in the thermal equilibrium scenario, relaxation to the thermal equilibrium state could be followed by a non-unitary quantum operation [30] and we have not assessed bounds in any such cases.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it is known that using ancilla qubits entangled with "system" qubits enhances the possibility of successful discrimination between unitaries [11] and it is conceivable that this could also yield a larger set of quantum algorithms and improved lower bounds in the thermal equilibrium case. Finally, in the thermal equilibrium scenario, relaxation to the thermal equilibrium state could be followed by a non-unitary quantum operation [30] and we have not assessed bounds in any such cases.…”
Section: Discussionmentioning
confidence: 99%
“…Together with proper temporal or spatial averaging procedures and evolution under spin interactions [23], the RF pulse can be specially designed to prepare any two-qubit computational base states, as well as their superpositions, starting from the thermal equilibrium state [2,[24][25][26].…”
Section: Measuring Quantum and Classical Correlations In Nuclear Magnmentioning
confidence: 99%
“…It has been shown that even with very low (or no) entanglement, quantum information processing can still be performed using nonclassical correlations as characterized by the presence of quantum discord [11,12]. However, computing and measuring quantum discord typically involves complicated numerical optimization and furthermore it has been shown that computing quantum discord is NP-hard [13].…”
Section: Introductionmentioning
confidence: 99%